Characteristics of humoral responses to the first coronavirus disease booster vaccine and breakthrough infection in central China: a multicentre, prospective, longitudinal cohort study - Xu, Junhong; Yuan, Youhua; Chen, Guohua; Ma, Bing; Zou, Yin Long; Wang, Baoya; Yan, Wenjuan; Zhang, Qi; Ma, Qiong; Mao, Xiaohuan; Wang, Huiling; Li, Yi; et al. (Frontiers in Immunology, 2025)
IntroductionThe long-term immunogenicity, adverse effects, influencing factors, and protection from booster vaccines remain unclear. Specifically, little is known regarding the humoral immunity and breakthrough infections associated with COVID-19 booster immunization. Therefore, we evaluated the immunogenicity, reactogenicity, influencing factors, and protective effects of the first coronavirus disease booster vaccine 23 months before and after implementation of dynamic zero epidemic control measures among healthcare staff.MethodsWe prospectively included 389 healthcare staff members in China with negative pre-enrolment severe acute respiratory syndrome coronavirus 2 test results. Neutralising serum antibodies were evaluated every two months till 23 months post-booster vaccination. Breakthrough infection was recorded or confirmed by SARS-CoV-2 specific PCR testing via throat swabs from participants before and after dynamic zero epidemic control measures.ResultsAt 15–30 days after vaccination, the mean concentration of the booster vaccine was 6.4 times above initial concentrations. Poorer antibody responses by booster vaccine correlated with male sex, longer post-booster duration, same-manufacturer vaccines, post-routine epidemic control measures implementation and intervals >210 days between primary and booster vaccinations. Higher breakthrough rates were associated with longer post-booster durations and post-routine epidemic control measures implementation but not associated with levels of neutralising antibodies after booster vaccination from participants. Adverse reactions were non-serious. These booster vaccine doses induced rapid, robust antibody responses, maintained for only 6–7 months.DiscussionNeutralizing antibodies induced by breakthrough infection with SARS-CoV-2 were weaker than those induced by the first COVID-19 booster vaccine, predicting that antibodies induced by SARS-CoV-2 may be very different from those of other known infectious pathogens.